Unexpected hemorrhage complications in association with celecoxib : Spontaneously reported case series after perioperative pain treatment in gynecological operations - Stammschulte, T.; Brune, Kay; Brack, A.; Augenstein, H.; Arends, G.; Gundert-Remy, U. (Anaesthesist, 2014)
A series of cases of postoperative bleeding were reported to the Drug Commission of the German Medical Association (Arzneimittelkommission der deutschen Ärzteschaft, AkdÄ) within the spontaneous reporting system after the regimen for postoperative pain treatment was changed from diclofenac (150 mg per day) to celecoxib (400 mg per day). All patients underwent elective gynecological surgery and 7 out of 11 patients with postoperative bleeding required revision surgery. Although alternative causes for the hemorrhage incidents could not be excluded, the documented circumstances could have been indicative of a possible causal association. Studies on perioperative pain treatment with celecoxib had previously shown no increased risk of hemorrhage. The tendency to hemorrhage observed in the registered cases could not be pharmacologically explained; however, due to the high dosages of celecoxib and the extensive co-medications used, a relative overdosing due to drug interactions or differences in the metabolism of the affected patients was conceivable. Celecoxib is not approved for the treatment of acute postoperative pain although a number of studies were carried out on the effectiveness and safety in patients undergoing surgery.
EVALuna2:8742